The Ritual Transfers of Properties. Languages of Semantics - the Real, the Categorial, the Verbai ones - Chervinsky, Piotr (Respectus Philologicus, 2004)
The article is devoted to a problem of internal parity of three semantic projections in the structure of sign-conceptual imaginations of native speakers of one or other language and consciousness (tradition, culture): 1) projection of the real, showing itself in conventional manipulative or ritual actions; 2) projection of the verbal, displayed first of all in the meaning of words and their roots, and also fixed in the language consciousness; 3) projection of the categorical - generalizing, classifying and grammatically interpreting the real and verbal systematically. The basis of internal similarity of the three named projections is supposed to be searched in the peculiarities of the structure and dynamics of the model described by five points (= phases), represented as a paradigmatic correlation of form meaning, displaying accordingly substantial, singulative, formal, modal and occasional components of the external and internal, the visible and invisible nature of a certain phenomenon, concept or subject. The analysis is made referring to explication of five-valences models, on material of so-called ’transfers of properties’ as a component of rites de passage, first of all wedding and funeral, and interpreted as a transitive model of a general model of achievement (purchase / deprivations, reception / disposals). The verbal projection of the researched system is illustrated in ’the forms of meaning’ of the Slavs root "-Bap-", displayed in various Slavic languages with an accent on valence determined by the character of the formed correlations.